Paisagem cultural da Serra da Piedade: Caeté/MG - Laura Beatriz Lage (2011)
This work investigates the idea of cultural landscape, the theoretical framework that holds the interaction between culture and environment, and how this idea is refuted in Brazil by the conservation agencies. The association of cultural heritage with nature began in 1956. In 1962, the General Conference of UNESCO, were drawn up recommendations to safeguard the aesthetic value of landscapes and sites, natural or manmade. The World Heritage Convention in 1992 recognized and protected cultural landscapes of outstanding universal value and the Global Strategy in 1998, proposed to link the criteria of natural and cultural heritage. The European Landscape Convention in 2000, adopted the concept of cultural landscape as part of a territory characterized by the action of natural and human factors and their interrelationships. (WINTER, 2007:53). In August 2007, the Instituto do Patrimônio Histórico e Artístico Nacional drafted the Cultural Landscape Charter and in september, the Cultural Landscapes and Geoparks Charter. But, analyzing the 25 Act of 1937, notes that this has already provided the precaution of these areas. This work analyzes the Conjunto Arquitetônico e Paisagístico of the Santuário de Nossa Senhora da Piedade, in Serra da Piedade, Minas Gerais, Brazil, listed as cultural heritage by three levels - local, state and federal - and received a proposal to expand its federal tipping area, adding value as Cultural Landscape.